Особливості накладення текстур у 3d-моделюванні - Тараненко, О. (My University, 2020)
In modern life, 3D modeling is an inseparable part of it, and to create a high-quality model, you need to impose a quality texture. This will give the model a realistic and attractive appearance
Keywords: текстура; 3D моделювання